Cover Image, Volume 77, Issue 10. Issue 10 (1st September 2021) - Liu, Tiansheng; Zhan, Xue; Yu, Yuan; Wang, Shaozhen; Lu, Cong; Lin, Guifang; Zhu, Xiangyu; He, Weiyi; You, Minsheng; You, Shijun
Abstract : The cover image is based on the Research Article Molecular and pharmacological characterization of biogenic amine receptors from the diamondback moth, Plutella xylostella by Tiansheng Liu et al., https://doi.org/10.1002/ps.6481 . Abstract : The cover image is based on the Research Article Molecular and pharmacological characterization of biogenic amine receptors from the diamondback moth, Plutella xylostella by Tiansheng Liu et al., https://doi.org/10.1002/ps.6481 .